USM LAUDS BAN ON VAPING IN CAMPUS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 22 December 2015 Universiti Sains Malaysia (USM) today expressed its full support for a blanket ban on electronic cigarettes (ecigarettes) or vape within its campus vicinity.